Treosulfan-Based Conditioning Regimen Prior to Allogeneic Stem Cell Transplantation: Long-Term Results From a Phase 2 Clinical Trial - Lazzari, Lorenzo; Ruggeri, Annalisa; Lupo Stanghellini, Maria Teresa; Mastaglio, Sara; Messina, Carlo; Giglio, Fabio; Lorusso, Alessandro; Perini, Tommaso; Piemontese, Simona; Marcatti, Magda; Lorentino, Francesca; Xue, Elisabetta; et al. (Frontiers in Oncology, 2021)
Introduction. Reducing toxicities while preserving efficacy in allogeneic stem cell transplant (allo-HCT) remains a particularly challenging problem. Different strategies to enhance the antitumor activity without increasing early and late adverse toxicities of the conditioning regimens have been investigated. Methods. The aim of “AlloTreo” prospective phase 2 clinical trial was to evaluate the efficacy and safety of a conditioning regimen based on Treosulfan (42 g/m2) and fludarabine (https://clinicaltrials.gov/ct2/show/NCT00598624). We enrolled 108 patients with hematological diseases who received a first allo-HCT between June 2005 and January 2011, inside the frame of this trial at our center. Median age at allo-HCT was 49 (21–69) years. Donors were HLA-matched related in 50 cases, 10/10-matched unrelated in 36, and 9/10-mismatched unrelated in 22. Graft-versus-host disease (GvHD) prophylaxis consisted of cyclosporine-A and methotrexate. Anti T-lymphocyte globulin (ATLG) was administered in patients receiving unrelated allo-HCT. Stem cell source was mainly peripheral blood stem cells (95%). Results. Conditioning regimen was well tolerated. Disease Risk Index was low in 14 (13%) patients, intermediate in 73 (67.7%), high in 17 (15.7%), and very high in 4 (3.7%). Full donor chimerism was documented for most patients (88%) at day +30. At 12 years overall survival (OS) was 41.7% (32.2%–50.9%), progression-free survival (PFS) 31.7% (23%–40.7%), GvHD-free/relapse-free survival 20.9% (13.7%–29.1%), cumulative incidence (CI) of relapse 44.5% (34.9%–53.6%), and transplant-related mortality (TRM) 22.5% (15.1%–30.9%). CI of acute GvHD grade II-IV was 27.8% (19.7%–36.5%) at 100 days; 12-year CI of chronic GvHD was 40.7% (31.3%–49.9%). Relevant long-term adverse effects were: 10 secondary malignancy, 3 fatal cardiovascular events, and one late-onset transplant-associated thrombotic microangiopathy. Ten successful pregnancies were reported after allo-HCT. In multivariate analysis, older age (≥60 years) at transplant (HR: 2.157, p=0.004) and a high/very high disease risk index (HR: 1.913, p=0.026) were significantly associated with a lower OS. Conclusions. Overall, our data confirmed the myeloablative potential and safe toxicity profile of full dose Treo (42 g/m2) especially for the younger population.